Axial strength test for round flat faced versus capsule shaped bilayer tablets. (12th November 2013) - Franck, Jason; Abebe, Admassu; Keluskar, Rekha; Martin, Kyle; Majumdar, Antara; Kottala, Niranjan; Stamato, Howard
Abstract: There has been increasing interest in fixed dose combination (FDC) therapy. Multi-layer tablets are a popular choice among various technologies to deliver FDCs. In most cases, round flat faced tooling is used in testing tablets as they have the simplest geometry. However, shaped tooling is more common for commercial products and may have an effect on bilayer tablet strength. Capsule shaped bilayer tablets, similar to a commercial image, and holders conforming to the tablet topology, were compared with similar round flat faced bilayer tablets and their corresponding holders. Bilayer tablets were subjected to an axial test device, until fracture and the quantitative breaking force value was recorded. As the second layer compression force increases, regardless of holder design, an increase in breaking force occurs as expected. This consistent trend provides insight regarding the breaking force of capsule shaped bilayer tablets. The results of this study show that at lower second layer compression forces, tablet geometry does not significantly impact the results. However, at higher compression forces, a significant difference in breaking force between tablet geometries exists. Therefore, using a test geometry close to the final commercial tablet image is recommended to have the most accurate prediction for tablet breakage.